If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(3y-3)+2y=8+2(6y-2)
We move all terms to the left:
-2(3y-3)+2y-(8+2(6y-2))=0
We add all the numbers together, and all the variables
2y-2(3y-3)-(8+2(6y-2))=0
We multiply parentheses
2y-6y-(8+2(6y-2))+6=0
We calculate terms in parentheses: -(8+2(6y-2)), so:We add all the numbers together, and all the variables
8+2(6y-2)
determiningTheFunctionDomain 2(6y-2)+8
We multiply parentheses
12y-4+8
We add all the numbers together, and all the variables
12y+4
Back to the equation:
-(12y+4)
-4y-(12y+4)+6=0
We get rid of parentheses
-4y-12y-4+6=0
We add all the numbers together, and all the variables
-16y+2=0
We move all terms containing y to the left, all other terms to the right
-16y=-2
y=-2/-16
y=1/8
| 12x+34+6x=46x-29 | | 2x-3+5×+2=90 | | F(n)=-3(n-1);-51 | | 9w-16.5=5.3 | | 2x+5=x/8 | | 5x2/3-10x=0 | | -n/3+10=21 | | -5y-1=-60 | | 16=–d+6 | | 2/3x-1/2=5/6x+2 | | 3x-23=7+9 | | 3x+6(x+4)=-21 | | 4x-8(0,8)=40 | | 2x/1-1=10 | | b/3+1/7=13 | | 75=1-y | | 1x-2/3=x+1/4 | | 2(1+8k)=-34+7k | | 0=3/2x+1/2 | | 5(x+1)=4x+6 | | 2/3b+4=6 | | 2x+12(2)=(x-2)2+16(2) | | 3x/2-1=11 | | 3/10x-2x+4/5=3/5 | | 2(w+3)-5(w-1)=32 | | 0.4x-0.5x-1=1 | | 5/6t+2/3t=54 | | |2x+3|=4x-1 | | 1+9n=4n+6 | | 2x12=-4 | | 33+3r=12+2r | | 7=w/8 |